SOSIALISASI TENTANG BANTUAN HUKUM SECARA CUMA-CUMA KEPADA MASYARAKAT DESA PLAOSAN, MAGETAN, JAWA TIMUR - Anik Tri Haryani; Sarjiyati; Sigit Sapto Nugroho (Universitas Merdeka Madiun, 2024)
The aim of this service is to provide understanding and insight to the public regarding providing free legal assistance. Free legal aid is legal services provided by advocates without receiving honorarium payments, including providing legal consultations, exercising power of attorney, representing, assisting, defending, and carrying out other legal actions for the benefit of indigent justice seekers. The method for implementing community service is divided into two stages, namely, the pre-activity stage and the implementation stage. The pre-activity stage involves conducting a preliminary survey of partners who will serve as places of service. The implementation stage is carried out with counseling/lectures then, followed by direct questions and answers and discussions related to community problems. After conducting outreach, the public understands free legal aid, where legal aid can also be provided for non-litigation cases (outside of court). To obtain legal aid, the applicant submits a written request for legal aid to the legal aid provider with the requirements specified in the Law. Legal assistance is not provided in criminal cases, including being suspected and/or accused of being involved in cases of abuse and/or illicit trafficking of narcotics, psychotropics and other addictive substances, terrorism, perpetrators of domestic violence, crimes against children, and crimes that threaten the integrity of the Unitary State of the Republic of Indonesia; in civil and state administrative cases, if the defendant is the Regional Government.